Reaching people receiving opioid agonist therapy at community pharmacies with hepatitis C virus: an international randomised controlled trial. Issue 12 (10th May 2022) - Byrne, Christopher J.; Radley, Andrew; Inglis, Sarah K.; Beer, Lewis; Palmer, Nicki; Duc Pham, Minh; Allardice, Kate; Wang, Huan; Robinson, Emma; Hermansson, Monika; Semizarov, Dimitri; Healy, Brendan; et al.
Summary: Background: Conventional healthcare models struggle to engage those at risk of hepatitis C virus (HCV) infection. This international study evaluated point‐of‐care (PoC) HCV RNA diagnostic outreach and direct‐acting antiviral (DAA) treatment for individuals receiving opioid agonist therapy (OAT) in community pharmacies. Aims: We assessed the effectiveness of a roving nurse‐led pathway offering PoC HCV RNA testing to OAT clients in community pharmacies relative to conventional care. Methods: Pharmacies in Scotland, Wales, and Australia were randomised to provide PoC HCV RNA testing or conventional referral. Pharmacists directed OAT clients to on‐site nurses (intervention) or local clinics (control). Infected participants were treated with DAAs, alongside OAT. Primary outcome was the number of participants with sustained virologic response at 12 weeks (SVR) and analysed using mixed effects logistic regression in the intention‐to‐treat (ITT) population. Results: Forty pharmacies were randomised. The ITT population contained 1410 OAT clients. In the conventional arm ( n  = 648), 62 (10%) agreed to testing, 17 (27%) were tested, 6 (35%) were positive and 5 (83%) initiated treatment. In the intervention arm ( n  = 762), 148 (19%) agreed to testing, 144 (97%) were tested, 23 (16%) were positive and 22 (96%) initiated treatment. SVR was obtained by 2 (40%; conventional) and 18 (82%; intervention). Intervention arm participants had higher odds of testing, OR 16.95 (7.07–40.64, p  < 0.001); treatment, OR 4.29 (1.43–12.92, p  = 0.010); and SVR, OR 8.64 (1.82–40.91, p  = 0.007). Conclusions: Nurse‐led PoC diagnosis in pharmacies made HCV care more accessible for OAT clients relative to conventional care. However, strategies to improve testing uptake are required. Trial registration: NCT03935906. Abstract : Relative to conventional care, opioid agonist therapy clients offered point‐of‐care hepatitis c virus RNA testing and treatment with DAAs at their community pharmacy had higher odds of being tested, starting treatment, and obtaining a cure.